Improving VIII-D Students' Active Participation and Vocabulary Achievement by Using Flash Cards at SMP Negeri 1 Rambipuji - Retno Andari Safitri; Zakiyah Tasnim; Sugeng Ariyanto (FKIP e-PROCEEDING, 2017)
Abstract: This research was conducted to solve the problems dealing with the students' active participation and vocabulary achievement process. The design of this research was Classroom Action Research. The research subjects were chosen by using purposive sampling. The data of this research were taken from the students' vocabulary test, observation checklist, interview, and documentation. From the result of the research, it was found that there were improvement from Cycle 1 and Cycle 2. In Cycle 1 the average of the students' active participation was 78,58% of the students who active participated in the teaching and learning process. The students' vocabulary test result showed that there were 77,14 of the students could achieve the minimum standard score, that was 75. In Cycle 2 85,71% of the students were categorized as active students. The students' vocabulary test result showed that there were 82,85% of the students were achieved the minimum standard score. It proved that the use of Flash Cardscould improve the students' vocabulary achievement. Key Words: Classroom Action Research, Flash Cards, Vocabulary Achievement.